Increasing customers’ loyalty. The contribution of marketing strategy, service quality and customer satisfaction - Themba, Orfyanny Syahreffy; Razak, Nurlaely; Sjahruddin, Herman (Archives of Business Research, 2019)
There are several factors that can increase consumer loyalty. This research was carried out on all consumers of Wuling cars who make a purchased and cars services until October 2018 at the sales office of PT. SGMW Motor Indonesia in Makassar City (South Sulawesi). So that the number of samples obtained is 153 customers. The results of the analysis of the Structural Equation Model using the help of analysis of moment structures 22 provide evidence that several factors have been shown to increase customer loyalty (i.e. marketing strategy and customer satisfaction). Service quality is only able to improve customer satisfaction. The practical implications of this study provide increased customers knowledge and management of PT. SGMW Motor Indonesia in Makassar City in increasing customer loyalty. The limitations of this study on the sample size that only using Wuling customers and only carried out in Makassar City, thus limiting the ability to generalize the research findings. The originality of this study provides a basis for the configuration of modeling development by using structural equation modeling and conceptual models that prove the influence of marketing strategy, service quality on customer loyalty by including customer satisfaction which in the previous study was carried out separately. The role of mediating customer satisfaction is proven to be able to increase customer loyalty in a high direction.